Evaluation of yield strength under small punch loading with different specimen thicknesses - Ferdous, I. U.; Nasrul Azuan, Alang; Juliawati, Alias; Norhaida, Ab Razak; Zureena, Abu Samah (Semarak Ilmu Publishing, 2025)
Distinguished by its simplicity and cost-effectiveness, Small Punch Test (SPT) enables the evaluation of different types of materials with reliable determination of their mechanical properties. In this study, the yield strength of Grade 91 steel is evaluated under the influence of different thicknesses involving three different yield loads (Py). A small punch finite element modelling approach was employed to examine the load-displacement (L-D) relationship of the Grade 91 steel. Different empirical relationships were used to determine the dependence of yield strength on specimen thickness. To determine the optimum specimen thickness, the yield load (Py) and the derived material correlation parameter were considered. Taking these factors into account, the recommended specimen thickness was determined. The predicted yield strength showed that the material correlation coefficient (α) strongly depends on the material and specimen’s thickness. The study found a range of 0.31≤ α ≤ 0.48 for Grade 91 steel. It was also found that the range for the appropriate specimen thickness for SPT is 0.4 mm - 0.75 mm.